Appraisal of the school health program in Urdaneta District I, Division of Pangasinan - Salazar, Nicanor M. 1934- (s.n.], 1969)
The objective of the study is to appraise the school health program of the elementary schools in the District of Urdaneta I of Pangasinan. The study aims to serve as an "eye opener" to all persons concerned regarding the breadth and width and depth of the school health program so they will be able to participate and assume their respective roles cooperatively and coordinately.